Removal of ammonium from municipal wastewater with powdered and granulated metakaolin geopolymer - Luukkonen, Tero (Environmental technology, 2018)
Ammonium [Formula: see text] removal from municipal wastewater poses challenges with the commonly used biological processes. Especially at low wastewater temperatures, the process is frequently ineffective and difficult to control. One alternative is to use ion-exchange. In the present study, a novel [Formula: see text] ion-exchanger, metakaolin geopolymer (MK-GP), was prepared, characterised, and tested. Batch experiments with powdered MK-GP indicated that the maximum exchange capacities were 31.79, 28.77, and 17.75 mg/g in synthetic, screened, and pre-sedimented municipal wastewater, respectively, according to the Sips isotherm (R2 ≥ 0.91). Kinetics followed the pseudo-second-order rate equation in all cases (kp2 = 0.04-0.24 g mg-1 min-1, R2 ≥ 0.97) and the equilibrium was reached within 30-90 min. Granulated MK-GP proved to be suitable for a continuous column mode use. Granules were high-strength, porous at the surface and could be regenerated multiple times with NaCl/NaOH. A bench-scale pilot test further confirmed the feasibility of granulated MK-GP in practical conditions at a municipal wastewater treatment plant: consistently <4 mg/L [Formula: see text] could be reached even though wastewater had low temperature (approx. 10°C). The results indicate that powdered or granulated MK-GP might have practical potential for removal and possible recovery of [Formula: see text] from municipal wastewaters. The simple and low-energy preparation method for MK-GP further increases the significance of the results